Diversity of Cultivated and Wild Medicinal Plants Used by People of Devdaha VDC of Rupandehi District, West Nepal - D. Tewari3, Anant Gopal Singh1*, K.N. Poudel2 and D. (Current Botany, 2011)
This study aims to explore the information on uses of medicinal plants found in Devdaha VDC of Rupandehi district, west Nepal. The study was conducted during January and October 2010. Information's on plant resources were collected interviewing key informants using a semi structured open ended questionnaires.Ã‚Â  Altogether 64 different species of plants belonging to 36 families were found used for medicinal purposes.